Advances in Hydroinformatics c - Gourbesville, Philippe; Cunge, Jean.; Caignaert, Guy.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2014)
The book is a collection of extended papers which have been selected for presentation during the SIMHYDRO 2012 conference held in Sophia Antipolis in September 2012. The papers present the state of the art numerical simulation in domains such as (1) New trends in modelling for marine, river & urban hydraulics; (2) Stakeholders & practitioners of simulation; (3) 3D CFD & applications. All papers have been peer reviewed and by scientific committee members with report about quality, content and originality. The target audience for this book includes scientists, engineers and practitioners involved in the field of numerical modelling in the water sector: flood management, natural resources preservation, hydraulic machineries, and innovation in numerical methods, 3D developments and applications.
Data & uncertainties in hydraulic modelling for engineering, specific applications of modelling -- New numerical methods and approaches for modelling systems -- 3D CFD and applications.
Keywords: Engineering; Hydraulic engineering; Engineering; Geoengineering, Foundations, Hydraulics; Hydrology/Water Resources; Geoengineering, Foundations, Hydraulics; Engineering Fluid Dynamics